Distribution of Eels (Anguilla sp.) in the Timang Tideng River, Alor Regency, NTT - Lora Sisilia Malailehi; Ade Y.H Lukas; Priyo Santoso (Journal of Marine and Coastal Science, 2022)
Eel (Anguilla sp.) is a fish that is classified as having a high economic value, with the level of distribution in almost all of Indonesia. The Timang Tideng River is one of the rivers located in the village of Kamaifui, Alor Regency, but until now, there has been no scientific report on the distribution of eel (Anguilla sp.) in the Timang Tideng River, Alor Regency, NTT. This study aims to determine the type and size of eel found in the Timang Tideng River. The research was conducted from March to April 2021 at three observation stations. Eel fishing is done at night considering its nocturnal nature. The fishing gear used is fishing rods and chicken stomachs as bait. Measurements of physical and chemical parameters of the waters were carried out simultaneously during the fishing process including temperature, pH, and current speed. The results showed that there were two types of eel in the Timang Tideng River, namely A. marmorata as many as 24 individuals and A. celebesensis as many as 1 individual. The eels found were in the yellow eel phase, with a total length range of 40-72 cm and a total weight ranging from 126-994 g.